Explaining Resource Nationalism. Issue 4 (23rd October 2017) - Pryke, Sam
Abstract: This article attempts to dissect the term resource nationalism (hereafter RN). It looks first at the origins of the term. Second, it examines various definitions of RN: in the business press where a zero sum conception of state and corporate interest is generally assumed, related definitions in academic writings that hinge on the relative control of resources by government and company, explanations that subsume the phenomenon within economic nationalism, accounts that stress how it restricts outputs and, finally, recent discussions that question prevailing understandings of RN and emphasise instead the diversity of its contemporary forms. The article then considers drivers of RN: the capture of economic rents, the corollary of the influence of market prices on this objective, obsolescing bargaining, the pressures of natural scarcity and the role of national identity. Fourth, the global context, commercial and legal, in which RN operates. Finally, the article considers the fluctuations in RN in recent years. Abstract : Resource Nationalism is an important component of national identities. In so far as there is discussion of this issue in both trade and academic writings on RN, analysts are either indifferent to popular concerns or see the sway of common attachments as indicative of the irrational appeal of the phenomenon.